A novel dynamic modeling method for aerostatic spindle based on pressure distribution. (December 2015) - Chen, Wanqun; Liang, Yingchun; Sun, Yazhou; Bai, Qingshun; An, Chenhui
The pressure distribution in an aerostatic bearing has an important effect on the performance of the associated mechanical equipment. To more accurately predict performance, a new dynamic modeling method has been developed that takes into account the pressure distribution in the bearing by integrating the principle of flow equilibrium and finite element theory. The direct corresponding relationship between the fluid film characteristics and spindle dynamic performance is established using this method. The simulation and experimental results show that the new dynamic modeling method for the aerostatic bearing is more efficient and reliable than traditional modeling methods.